Persistent elbow instability requiring acute ligament reconstruction after simple traumatic dislocation: A case report - Rodriguez-Materona, Solangel; González Chávez, Raúl Ernesto; Valbuena Bernal, Felipe José (Revista Colombiana de Ortopedia y Traumatología, 2022)
Introduction: Elbow dislocation is a frequent emergency room event. Elbow dislocation diagnosis is based on clinical and radiological examination. The management frequently consists on closed reduction. Occasionally, persistence of instability after reduction becomes a challenge for the physician. Case report: We present the case of a 58-year-old male who required acute surgical intervention due to persistent simple elbow dislocation. The patient had three unsuccessful closed reduction attempts. Although bone involvement was ruled out, the evidence of inadequate joint reduction was the indication for emergent ligament reconstruction. Results: The patient required open surgical management for ligament reconstruction. After 6 months of follow-up, the patient presents with slight elbow stiffness due to a total range of motion of 50◦. The patient did not present new episodes of re-dislocation after ligament reconstruction. Discussion: Simple dislocation is the most frequent form of elbow dislocation. Considering joint stability after a closed reduction is very important. A minority of patients require surgical procedures to restore the ligamentous and muscular stabilizers of the elbow. An analysis of the case and the most important aspects are highlighted under the evidence of the literature.